The Effect Of The Cooperative Team Quiz Model On The Problem-Solving Skills Of Students In Grade VII Of SMP Negeri 1 Simpang Tiga Pidie - Nadiatul Husna; Mauliana Wayudi; Surya Darni (STMIK Indonesia Banda Aceh, 2026)
This study aims to determine the effect of the Cooperative Team Quiz learning model on the problem-solving skills of seventh-grade students of SMP Negeri 1 Simpang Tiga. This study uses a quantitative approach with a Quasi-Experimental design. The research sample consists of two classes, namely the experimental class taught using the Cooperative Team Quiz model and the control class taught using conventional methods. The research instrument in the form of a pre-test and post-test was used to measure students' problem-solving skills. The results showed a significant increase in students' problem-solving skills in the experimental class compared to the control class. Statistical tests proved that the Cooperative Team Quiz model had a positive and significant effect in improving problem-solving skills. Thus, this model is effective to be used as a learning strategy to improve junior high school students' problem-solving abilities.